2007
DOI: 10.3168/jds.s0022-0302(07)72622-x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical and Clinical Mastitis in Heifers Following the Use of a Teat Sealant Precalving

Abstract: This study investigated the effect in heifers of infusion of a bismuth subnitrate teat-canal sealant and bacterial intramammary infection (IMI) precalving on prevalence of postcalving IMI and incidence of clinical mastitis in the first 2 wk postcalving. Glands (n = 1,020) from heifers (n = 255) in 5 seasonally calving, pasture-fed dairy herds were randomly assigned within heifer to 1 of 4 treatment groups (no treatment; mammary gland secretion collection; infusion of a teat sealant; or sample collection with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
3
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 45 publications
4
43
3
7
Order By: Relevance
“…These results are in agreement with different studies that observed lower infection rates in the group that received the internal seal (Berry & Hillerton 2002, Godden et al 2003, Parker et al 2007. Rabiee & Lean (2013), in a meta-analysis study about the efficiency of internal seal associated or not to dry cow antibiotic, concluded that the use of internal seal reduces the risk of IMI by 25% immediately postpartum when compared to the use of only antibiotic during the dry off period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with different studies that observed lower infection rates in the group that received the internal seal (Berry & Hillerton 2002, Godden et al 2003, Parker et al 2007. Rabiee & Lean (2013), in a meta-analysis study about the efficiency of internal seal associated or not to dry cow antibiotic, concluded that the use of internal seal reduces the risk of IMI by 25% immediately postpartum when compared to the use of only antibiotic during the dry off period.…”
Section: Discussionsupporting
confidence: 91%
“…These facts reflect positively on the reduction of somatic cell count (SCC) and cases of clinical mastitis in the first 100 days of lactation. The same effects were observed for postpartum heifers that received internal seals during pre-partum (Parker et al 2007(Parker et al , 2008.…”
Section: Introductionsupporting
confidence: 66%
“…aureus NIMI. Parker et al (2007) found that heifers with precalving CNS IMI had an increased risk of postcalving IMI with Staph. aureus (RR = 6.56; 95% CI = 1.4-31.7).…”
Section: Minor Pathogensmentioning
confidence: 99%
“…In several heifer mastitis surveys conducted throughout the world, up to 60% of the quarters harbored an IMI at the time of calving (e.g. Cook et al 1992;Parker et al 2007;Piepers et al 2010). Most of these IMI reveal themselves as subclinical mastitis characterized by an elevated SCC without any other visible symptoms of inflammation (De Vliegher et al 2012).…”
Section: High Scc In Fresh Heifers ('High Fresh Heifers')mentioning
confidence: 99%